The Effectiveness of Using Dual Situated Learning Model (DSLM) to Teach Physics in the Development of Conceptual Comprehension of Secondary School Male Students - Hamdi, Abdulaziz Mohammed (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to detect the effectiveness of using a dual situated learning model (DSLM) to teach physics in the development of conceptual comprehension of secondary school male students. In order to achieve the objective of the study, the semi-experimental design was based on experimental method. The study sample consisted of (77) second grade secondary school male students in Jazan province. The sample was randomly divided into two groups. The experimental group consisted of (39) students who studied using a dual situated learning model (DSLM), and the control group consisted of (38) students group who studied using the conventional method. The results of the study were statistically significant between the mean scores of the experimental and control groups in the post-application of the conceptual comprehension test in favor of the experimental group. In light of these results, the study recommended that use of the dual situated learning model (DSLM) in teaching and learning physics for secondary school students. The study also recommended holding training courses and programs, and workshops to train physics teachers on the use and application of a dual situated learning model (DSLM) during planning and implementation of lessons. The study proposed carrying a similar study examining different thinking skills and different school stages.